Advancing agricultural greenhouse gas quantification - Olander, L; Wollenberg, Eva Karoline; Tubiello, F.N.; Herold, Martin (IOP Publishing, 2013)
Better information on greenhouse gas (GHG) emissions and mitigation potential in the agricultural sector is necessary to manage these emissions and identify responses that are consistent with the food security and economic development priorities of countries. Critical activity data (what crops or livestock are managed in what way) are poor or lacking for many agricultural systems, especially in developing countries. In addition, the currently available methods for quantifying emissions and mitigation are often too expensive or complex or not sufficiently user friendly for widespread use.